2022
DOI: 10.1111/jcpp.13701
|View full text |Cite
|
Sign up to set email alerts
|

Facial reactions to emotional films in young children with conduct problems and varying levels of callous‐unemotional traits

Abstract: Background: Elevated levels of callous-unemotional (CU) traits have proven useful for identifying a distinct subgroup of children whose conduct problems (CP) are early emerging, severe, persistent, and underpinned by aberrant emotional processing. The early childhood emotional experiences and expressions of CP subtypes are poorly understood, despite their importance to understanding the problematic attachments and atypical social affiliation experienced by children with elevated CU traits. The current study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Similar to the ICU, the CAPE manual operationalizes the shallow/deficient affect symptom as incongruent affect to situations and a lack of intense emotions except in an ingenuine way or to benefit oneself. A recent study found that 3-to 5-year-old children with elevated LPE had more incongruent facial emotional responses to sad and happy film clips than typically developing children, but this incongruence of emotion to situations did not differ significantly from children with conduct problems but without LPE (Kimonis et al, 2023). It is possible that differences in emotional deficits may be too subtle to be apparent to outward observers.…”
Section: Lpe Symptoms In Young Children Can Be Reliably Coded Between...mentioning
confidence: 97%
“…Similar to the ICU, the CAPE manual operationalizes the shallow/deficient affect symptom as incongruent affect to situations and a lack of intense emotions except in an ingenuine way or to benefit oneself. A recent study found that 3-to 5-year-old children with elevated LPE had more incongruent facial emotional responses to sad and happy film clips than typically developing children, but this incongruence of emotion to situations did not differ significantly from children with conduct problems but without LPE (Kimonis et al, 2023). It is possible that differences in emotional deficits may be too subtle to be apparent to outward observers.…”
Section: Lpe Symptoms In Young Children Can Be Reliably Coded Between...mentioning
confidence: 97%
“…Facial expressions have been analysed for various applications. However, not all the facial regions contribute to expression detection, and a few areas do not change with varied terms [11,12]. Determining human behaviour from facial expressions is an excellent application in healthcare, tourism and hospitality, and the retail industry.…”
Section: Related Workmentioning
confidence: 99%
“…It is calculated for each pixel value in the input image. Te gradient x is computed by equation ( 11) and gradient y is computed by equation (12) in which R and C represent the row and column of each image matrix A. After the gradient value computation of each pixel in the image, the magnitude and angle values are computed by equations ( 13) and (14).…”
Section: Face Detectionmentioning
confidence: 99%